Effect of Lightning Strikes on Wind Turbine Blade Life. - Severino, Christopher. (2017)
Abstract: Understanding the effects of lightning strikes on wind turbines becomes increasingly important as the size and rated power of wind turbines increase and as they are placed in locations where repair is difficult and costly, especially for offshore applications. When the lightning strikes, it can locally increase material temperature at the strike zone, inducing high compressive localized strains. The severity of this thermally induced strain depends on the thermal conductivity of strike zone material and the surrounding material. The aim of this paper is to develop a methodology to predict blade residual life after a known number of lightning strikes and to understand the structural integrity threshold due to such damage. Such data will help the wind community to develop sensor specification and predictive methods for blade life after each lightning strike. Thermomechanical stresses and heat transfer cases are used to simulate the lightning strike blade model and it is analyzed through the use of a commercial finite element code. A combined thermal and stress analysis of a lightning strike model of typical wind turbine blade material (including E-glass composite layups) shows that the fiberglass material immediately surrounding the lightning attachment location becomes damaged due to plastic deformation. Depending on the magnitude and number of lightning strikes, the blade has the potential to fail under an extreme static gust load, under fatigue, or a combination of the two. It is therefore crucial to understand the reduced material property limits resulting from lighting strikes. It is hoped that this study will provide a useful guideline for designing lightning protection systems and predicting blade life, especially for offshore wind turbines where lightning strikes are statistically more commonplace.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Behrouz Abedian.; Committee: Behrouz Abedian, Shu Quek, Vincent Manno, and Chandra Yerramalli.; Keyword: Mechanical engineering.